Structural and Optical Properties of Bismuth-doped Cerium Oxide Prepared at a Low Temperature - Paramita, Safira Arta; Nurhasanah, Iis; Khumaeni, Ali (Universitas Negeri Surabaya, 2023)
Cerium oxide (CeO2) is a functional material with excellent physicochemical properties. Its properties can be modified by doping with different elements, including bismuth, which can be done through various synthesis methods. The precipitation method combined with ultrasonic radiation was used to synthesize bismuth-doped cerium oxide (CeO2:Bi) at a low temperature of 200oC. In this study, we investigate the alteration of structural and optical properties of as-prepared CeO2:Bi by subjecting it to additional calcination at a high temperature of 500oC. The structural and optical properties of CeO2:Bi were characterized using thermal gravimetric analysis, X-ray diffraction, Scanning Electron Microscope-Energy Dispersive X-Ray, Fourier Transform Infrared spectroscopy, and UV-Visible spectroscopy. The additional calcination produced a less significant weight-loss percentage than the as-prepared CeO2:Bi observed from the gravimetric curve. The Fourier transform infrared spectrum revealed the loss of a small number of hydroxyl molecules trapped on the CeO2:Bi surface when additional calcination was subjected. Based on the X-ray diffraction spectra, additional calcination results in the smallest crystallite size and compressive strain without the changed cubic crystal structure of CeO2:Bi. The successful doping of Bi in CeO2 was confirmed by the composition analysis from Energy Dispersive X-Ray measurement. Scanning electron microscope image showed spherical and agglomerated particles of calcined CeO2:Bi. The optical properties of both CeO2:Bi possessed similar trend absorption spectra and almost the same band gap energy. The results indicated that the calcination of as-prepared CeO2:Bi at a temperature of 500oC did not affect its structural and optical properties significantly. Thus, combining ultrasonic radiation with precipitation is an advantageous method to synthesize at a low temperature of stable CeO2:Bi crystalline.